DAVID LACK: TWO VERSIONS OF SPECIATION, FROM NEUTRALISM TO THE ADAPTIVE APPROACH - Ya. M. Gall (Вавиловский журнал генетики и селекции)
The article reviews the development of two leading concepts of speciation, developed in the 1940-s by the British ornithologist and ecologists David Lack (1910–1973). It shows the ways Lack simultaneously developed two different versions of speciation. Emphasis is placed on the analysis of evolutionary thoughts of Lack expressed in his book “Darwin’s Finches”. Evidence is given that Lack, in addition to being a founder of contemporary evolutionary ecology, apparently belongs to the architects of evolutionary synthesis.